A Bacterial Extract of OM-85 Broncho-Vaxom Prevents Allergic Rhinitis in Mice. Issue 2 (March 2014) - Han, Ling; Zheng, Chao-Pan; Sun, Yue-Qi; Xu, Geng; Wen, Weiping; Fu, Qing-Ling
Background: According to the hygiene hypothesis, bacterial infections during early life contribute to a reduced incidence of asthma in animals. However, the effects of microbial products at a safe dose and within a rational time course on the prevention of allergic rhinitis (AR) have been inconclusive. This study investigated the immunomodulatory effects of oral administration of a bacterial extract, OM-85 Broncho-Vaxom (BV), with a low dose and general time course, which is currently used for respiratory infections in humans, on AR inflammation in mice. Methods: We developed a mouse model of ovalbumin (OVA)-induced AR allergic inflammation in the nose mucosa of mice. Low doses of OM-85 BV were orally administered for 3 months (long term) before sensitization. We evaluated nasal symptoms, pathology in the nose, inflammatory cells, and the levels of T helper 1 (Th1)/Th2 cytokines in the nasal lavage fluids, and the serum levels of specific IgE and IgG1. We also observed enhanced effects of OM-85BV with 1 month (short term) of treatment. Results: We found that long-term pretreatment with OM-85 BV protected the mice from the majority of allergy-specific symptoms; specifically, OM-85 BV suppressed nasal symptoms, inhibited eosinophil infiltration in the nose, inhibited inflammatory infiltrates and the Th2 response by reducing cytokines (IL-4, IL-5, or IL-13) in the nasal lavage fluids, and reduced IgE and IgG1 levels. Furthermore, short-term treatment with OM-85 BV decreased the levels of Th2 cytokines and IgE. Conclusion: Taken together, our data suggested that OM-85 BV is a low-cost alternative candidate to prevent AR with simple oral administration.